2010
DOI: 10.2304/power.2010.2.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Trusting Trust in the Context of Higher Education: The Potential Limits of the Trust Concept

Abstract: There is a convincing body of empirical evidence supporting the benefits of trust. A number of recent publications have paid a great deal of attention to possible negative consequences of the trusting process, but there has been little interdisciplinary focus on the potentially unconstructive aspects of the trusting process between learners and teaching authorities. The authors argue here that unmonitored student trust in a teacher's expertise in the context of higher education might sabotage the use and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Focus on leadership contributions towards achieving the SDG objectives by assessing the levels of emphasis on the SDGs, setting targets for achieving the SDGs, and assessing the progress in terms of achieved goals. However, Kovač and Kristiansen (2010) warn that, in the specific context of higher education and particularly regarding the teaching practice, overconfidence and the absence of monitoring can be counterproductive in the development of cognitive and critical thinking skills. The authors advise that the potentially negative consequences of overconfidence should be guarded against.…”
Section: Wwwrichtmannorgmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus on leadership contributions towards achieving the SDG objectives by assessing the levels of emphasis on the SDGs, setting targets for achieving the SDGs, and assessing the progress in terms of achieved goals. However, Kovač and Kristiansen (2010) warn that, in the specific context of higher education and particularly regarding the teaching practice, overconfidence and the absence of monitoring can be counterproductive in the development of cognitive and critical thinking skills. The authors advise that the potentially negative consequences of overconfidence should be guarded against.…”
Section: Wwwrichtmannorgmentioning
confidence: 99%
“…The authors advise that the potentially negative consequences of overconfidence should be guarded against. Among these, Kovač and Kristiansen (2010) highlight the "[...] use of heuristics at the expense of systematic processing, the feeling of complacency that invites cognitive inertia, the difference between practising traditional versus progressive types of teaching, the amplification of already uneven power relations, and the possibility of social exclusion" (p. 284).…”
Section: Wwwrichtmannorgmentioning
confidence: 99%
“…Moreover, others indicated that researchers should look beyond the positive impacts of trust and look deeper into its negative impacts (Zahra et al , 2006). Kovač and Kristiansen (2010) argued that an optimal level of trust exists, which indeed has a good outcome, but, might, after a certain point move to an excessive level of trust which may, in turn, yield negative impacts on the ability to process information and examine it critically (Gargiulo and Ertug, 2006). (Skinner et al , 2014), argued that sometimes a trustee's reluctance to be trusted by the trustor can lead the trustee to act in a manner that he/she is not prepared for, but are forced into, leading to a “trap of obligation” (Wang and Huang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Associated with these three personal attributes, Mayer not found in the context or situation of what each of these personal attributes becomes most sensitive and critical (Shooter, Paisley, & Sibthorp, 2012). In the context of higher education, it is found that excessive trust in teachers' expertise hampers cognitive skill and critical thinking ability of the student (Kovač & Kristiansen, 2010). Furthermore, in the context of romantic relationship, how an individual trusts his or her intimate partner is not solely determined by the personal attributes of trustee-he or she even may be more inclined to ignore-but also related to the meaning given in the experience with the intimate partner and attributional processes influenced by the individual characteristics of trustor, such as attachment style, self-esteem, and selfidentity (Miller & Rempel 2004).…”
Section: Introductionmentioning
confidence: 99%